2013
DOI: 10.7150/ijms.7027
|View full text |Cite
|
Sign up to set email alerts
|

Shifting towards an Opt-Out System in Greece: A General Practice Based Pilot Study

Abstract: New legislation in Greece towards presumed consent for organ donation, effective as of June 2013, has come at a critical moment. This pilot study aims to explore awareness, specific concerns and intentions about the new organ donation framework among patients attending Greek general practices in a rural and urban setting. Only 2.6% of respondents had a donor card, a mere 9.6% was aware of new legislation, whereas only 3.8% considered that the public had been adequately informed. Higher income respondents were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…In another Greek general practice study, patients with a donor card accounted for only 2.6%, with one out of four intending to carry out their right to prohibit organ removal upon death 17. The strong association between possession of an organ donor card (informed group) and the willingness to donate organs has been shown in a German study among public officials 33.…”
Section: Discussionmentioning
confidence: 94%
“…In another Greek general practice study, patients with a donor card accounted for only 2.6%, with one out of four intending to carry out their right to prohibit organ removal upon death 17. The strong association between possession of an organ donor card (informed group) and the willingness to donate organs has been shown in a German study among public officials 33.…”
Section: Discussionmentioning
confidence: 94%
“…In the year of transition, a survey of primary care patients reported that very few were aware of the organ donation legislation change, and more than 20% of respondents intended to prohibit the removal of their organs upon death. 2 Lack of focused information and low awareness may lead to informal interactions in closely knit communities, possibly resulting to greater optout rates. 2 In a multiethnic area of south London, reluctance among some groups to donate outside their narrow community may also increase the gap between the need for organs and their availability.…”
Section: Organ Donation and New Policies: Do We Need To Act Less Genementioning
confidence: 99%
“…2 Lack of focused information and low awareness may lead to informal interactions in closely knit communities, possibly resulting to greater optout rates. 2 In a multiethnic area of south London, reluctance among some groups to donate outside their narrow community may also increase the gap between the need for organs and their availability. 3 Furthermore, it has been hypothesized that sociocultural features of communities may greatly influence perceptions of organ donation enhancing diversity.…”
Section: Organ Donation and New Policies: Do We Need To Act Less Genementioning
confidence: 99%
See 1 more Smart Citation
“…Reaching the public with information and support is more important than ever, with changes in the legislation coming up. When evaluating the introduction of an opt-out system in Greece, this also became apparent (53). Only 3.8% of the citizens considered the public to be adequately informed.…”
Section: Organ Donation Educationmentioning
confidence: 99%